Information Accounting System on Small and Medium Enterprises: Bibliometric Analysis - Nugraha, Ginanjar Adi; Firmansyah, Irman; Dinanti, Aldila (Pusat P2M Politeknik Negeri Batam, 2025)
This research aims to investigate publication trends on the topic of accounting information systems in SMEs. This is intended to fill the research gap regarding the absence of previous research that discusses the development of publications on this topic. The method used is bibliometric analysis with the Scopus database in the publication range from 2014 to 2023. The search keywords use Bolean, namely